Enrichment of Genetic Linkage Maps and Mapping QTLs Specific to Seed Strength-Hardness/Softness-In Guava (Psidium guajava L.) - B Padmakar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
The present research focuses mainly on molecular mining and morphological evaluation of guava genome within a full-sib population and, thereby, mapping of quantitative trait loci related to fruit quality traits, viz., seed strength (hardness/softness) and average fruit weight. Linkage maps were enriched for both parental lines, 'Kamsari' and 'Purple Local' using a set of 60 RAPD markers following the pseudo-testcross strategy on a panel of 94 progeny. A total of 480 scorable markers were identified, of which 131 were specific to 'kamsari' and 28 to 'Purple Local', segregating as test cross markers, and, 321 showing intercross pattern common to both. 'Kamsari' spanned a total length of 1959.1cM with average marker interval distance of 3.93cM, while 'Purple Local' spanned a length of 1537.9cM with average marker interval distance of 3.29cM, by forming 11 linkage groups. Estimated genome length observed was 93.02% and 92.77% in 'Kamsari' and 'Purple Local', respectively. Composite Interval Mapping (CIM) was computed at significance of 0.05 and LOD threshold greater than 3.0, which led to detection of one major QTL for the trait of average fruit weight, and, four QTLs for the trait of seed strength (hardness/softness). Of these, two were major and two minor QTLs. Our study provides molecular mapping information on marker-assisted selection for improvement of guava in a breeding program.